Formulation and evaluation of floating tablet of H2-receptor antagonist. (September 2015) - Kesarla, Rajesh S.; Vora, Pratik Ashwinbhai; Sridhar, B. K.; Patel, Gunvant; Omri, Abdelwahab
Abstract Context: Conventional sustained dosage form of ranitidine hydrochloride (HCl) does not prevent frequent administration due to its degradation in colonic media and limited absorption in the upper part of GIT. Objectives: Ranitidine HCl floating tablet was formulated with sublimation method to overcome the stated problem. Methods: Compatibility study for screening potential excipients was carried out using Fourier transform infrared spectroscopy (FT-IR) and differential scanning chromatography (DSC). Selected excipients were further evaluated for optimizing the formulation. Preliminary screening of binder, polymer and sublimating material was based on hardness and drug release, drug release with release kinetics and floating lag time with total floatation time, respectively. Selected excipients were subjected to 32 factorial design with polymer and sublimating material as independent factors. Matrix tablets were obtained by using 16/32" flat-faced beveled edges punches followed by sublimation. Results: FT-IR and DSC indicated no significant incompatibility with selected excipients. Klucel-LF, POLYOX WSR N 60 K and l-menthol were selected as binder, polymer and sublimating material, respectively, for factorial design batches after preliminary screening. From the factorial design batches, optimum concentration to release the drug within 12 h was found to be 420 mg of POLYOX and 40 mg of l-menthol. Stability studies indicated the formulation as stable. Conclusion: Ranitidine HCl matrix floating tablets were formulated to release 90% of drug in stomach within 12 h. Hence, release of the drug could be sustained within narrow absorption site. Moreover, the dosage form was found to be floating within a fraction of second independent of the pH of media ensuring a robust formulation.